Pint of no return : a shake shop mystery - Mentink, Dana (Mentink, Dana. Shake shop mystery., 2021)
"The first in new dessert cozy mystery series! A murder in town is bound to shake things up... After her divorce from her thrice-married embezzler husband, Trinidad Jones is finally ready for a fresh start. So when she's left one of ex's businesses in Upper Sprocket, Oregon, she decides to pack up her dog, cash in her settlement, and open her dream business: the Shimmy and Shake Shop, introducing the world to her monster milkshakes. And even with a couple sticky situations underway, namely that the other two ex-wives also call Sprocket home, Trinidad's life seems to be churning along smoothly. That is, until she discovers her neighbor, the Popcorn King, head down in his giant popcorn kettle. When one of Trinidad's fellow ex-wives is accused of the murder and Upper Sprocket descends into mayhem, it's going to take a supersized scoop of courage to flush out the killer"--